Prakiraan Penggunaan Volume Air PDAM Kota Malang Menggunakan Metode Support Vector Regression dengan Ant Colony Optimization - Akmilatul Maghfiroh; Agus Wahyu Widodo; Yuita Arum Sari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Water is a very important element in the life of all living things. Humans need water to survive and carry out daily activities. Regional Drinking Water Company (PDAM) is a Regional-Owned Company (BUMD) that provides clean water for every region in Indonesia, one of them is PDAM in Malang. The population continues to grow every year causing an increase in the need for clean water. Considering the increasing need for clean water and limited water sources, PDAM Malang must distribute the water optimally and efficiently so that consumers can fulfill their needs for clean water. Therefore, by forecasting the water volume that can be used, it is hoped that it can help PDAM Malang to estimate the volume of water that needs to be distributed efficiently and on target. Some water forecasting methods such as